Effect Of Different Incubation Temperatures To The Rate Of Catfish (Mystus nigriceps) Yolk Absorption - Putri, Hylda Khairah; ', Sukendi; ', Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was held on March, 2016 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine Science, University of Riau Pekanbaru. The purpose of this research was to determine the effect of different incubation temperatures to the rate of yolk absorption, rate of growth in length, the efficiency of yolk utilization, survival of endogenous feeding phase and to know the right time to start feeding in the larval Catfish (Mystus nigriceps) stage. The research method used in this research was complete randomized design (CRD) with one factor, four treatment temperatures which were 260C, 280C, 300C and 320C and three replications.The results showed the highest rate of yolk-sac absorption was at temperature of 320C 20,07% (52 hours) but the maintenance medium temperatures 28°C and 30°C was the best temperatures for the rate growth in length, efficiency of yolk utilization and survival of endogenous feeding phase.Key words: Mystus nigriceps, temperature, yolk absorption